The sex ratio, Gonadosomatic Index and Fecundity of the Copper Mahaseer, Neolissochilus hexagonolepis (Mc Clelland, 1839) from Tamor river, Nepal - Subba, S.; Mahaseth, V. K. (Nepalese Journal of Biosciences, 2015)
The sex ratio, Gonado Somatic Index and fecundity of the Copper Mahseer, Neolissochilus hexagonolepis were investigated. The sex ratio was 1:1.2 (Male to female). The gonado-somatic index ranged from 0.084 % to 16.47 % for female fish and 0.086% to 5.81 % for male fish. The highest mean GSI 9.037 % was recorded in July for female fishes and the highest 2.838 % was recorded in September for male fishes. The total weight and total length of the fishes had strong positive correlation. Also, the correlation between the weight of gonad and GSI was positively correlated. Absolute fecundity ranged from to 11424. Fecundity had strong positive correlation with total length (r = 0.98), total weight (r= 0.9) and total length (r= 0.88).